Jail Officers’ Adherence to Traditional Bases of Social Power: Understanding Inmate Control in a Unique Correctional Context - Applegate, Brandon K. (The prison journal, 2023)
Scholars have investigated the social sources of power that correctional officers embrace as their means of control over people who are incarcerated. However, this work has been conducted with community correctional officers and those working in state prisons, with almost no attention to officers who work in local jails. Jails are distinctive in ways that may be important for the bases of power on which officers may draw, and the current study analyzed data from officers employed by a large urban jail. Jail officers favored coercive power more so and referent power less so than has been reported in prior studies of prison officers. Further, we employed latent class analysis to identify groups of officers and analyzed covariates of the resultant classes. We discuss implications for understanding the exercise of power in local jails.